The use of renin angiotensin aldosterone system inhibitors may be associated with decreased mortality after cancer surgery - Ah Ran Oh (Scientific Reports, 2022)
Abstract Renin–angiotensin–aldosterone system (RAAS) inhibitors are antihypertensive agents with conflicting results on protective effects against some types of cancer. In light of these controversies, we aimed to study the effects of RAAS inhibitors in patients undergoing cancer surgery. From March 2010 to December 2019, consecutive adult patients with antihypertensive drug prescription at discharge after cancer surgery were enrolled and divided into two groups according to RAAS inhibitors prescription. The primary outcome was 5-year mortality after surgery. Secondary outcomes included mortalities during 3-year and 1-year follow-ups and cancer-specific mortality and recurrence rates during 5-, 3-, and 1-year follow-ups. A total of 19,765 patients were divided into two groups according to RAAS inhibitor prescription at discharge: 8,374 (42.4%) patients in the no RAAS inhibitor group and 11,391 (57.6%) patients in the RAAS inhibitor group. In 5022 pairs of propensity-score matched population, 5-year mortality was significantly lower in the RAAS inhibitor group (11.4% vs. 7.4%, hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.64–0.83, P < 0.001), and 5-year recurrence rate was also lower for the RAAS inhibitor group (5.3% vs. 3.7%, HR 0.82, 95% CI 0.68–0.99, P = 0.04). In our analysis, RAAS inhibitor was associated with decreased 5-year mortality in hypertensive patients who underwent cancer surgery. Prescription of RAAS inhibitor in accordance with current guidelines may be associated with improved mortality after cancer surgery.